Tipologi Motivasi Intrinsik Siswa Sekolah Dasar dengan Gaya Belajar Kinestetik - Khusnah, Deva Amirotul; Tirtoni, Feri (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
This study aims to describe the forms or characteristics of intrinsic motivation and identify the typology of intrinsic motivation among elementary school students with kinesthetic learning styles. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects were fourth grade students at SD Muhammadiyah 5 Porong who had a tendency toward kinesthetic learning styles. The result show that students’ intrinsic motivation is evident through their intiative to learn, freedom of self expression, perseverance in completing tasks, and ability to choose learning methods that suit their comfort level. In addition, three types of intrinsic motivation were found, namely active independence, competence and perseverance, and social collaboration. These findings indicate that students’ intrinsic motivation develops when their needs for autonomy, competence, and social connectedness are met through practice-based learning. This study is expected to serve as a reference for teachers in designing learning that is in line with the characteristic of studentss’ learning styles.